The Increasing Business Eco-Efficiency and Competitive Advantage through the Application of Green Accounting - Meta Ardiana; Rachma Agustina; Dwi Ari Pertiwi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
The global ecological crisis caused by environmental damage due to the continuous exploitation of natural resources and the environment and not thinking about long-term sustainability is worsening and worrying. This is one of the driving aspects of the emergence of green accounting. The agro-industry sector is a sector that is vulnerable to environmental issues because it is closely related to the use of pesticides, concentrates, air quality pollution, use of fuel for its distribution, etc. This is what makes researchers interested in researching the Lumintu Farm Kediri Regency. This study examines how using green accounting increases eco-efficiency and competitive advantage. A comparison ratio of value added to environmental performance is used to analyze eco-efficiency. Data collection methods include literature study, observation, interviews, and documentation. The validity of the data is checked through the extension of participation, the persistence of words, and the triangulation of data. The findings demonstrated that Lumintu Farm had adopted green accounting through the stages of identifying costs for mitigating the impact of harmful externalities on production, recognition, measurement, presentation through the income statement, and disclosure of the costs or costs incurred by the company for environmental management. Eco-efficiency analysis with environmental performance and financial performance ratios shows positive results, 52%, an increase of 54%, and a rise of 2%. Implementing green accounting through a consistent allocation of environmental costs improves environmental performance and the entity’s profit. With this profit, business continuity will be better in increasing livestock growth.